Pulmonary Mycobacterium avium infection demonstrating unusual lobar caseous pneumonia. Issue 5 (5th July 2016) - Okuzumi, Shinichi; Minematsu, Naoto; Sasaki, Mamoru; Ohsawa, Kazuma; Murakami, Marohito
Abstract : Mycobacterium avium complex (MAC) infection is a major medical concern in Japan because of its increased prevalence and associated mortality. A common radiological feature in pulmonary MAC infection is a mixture of two basic patterns: fibrocavitary and nodular bronchiectatic; however, lobar consolidation is rare. We report an 83‐year‐old man with lobar caseous pneumonia caused by pulmonary MAC infection. Radiological findings were predominantly composed of dense lobar consolidation and ground‐glass opacity. A diagnosis was made in accordance with the clinical and microbiological criteria set by the American Thoracic Society. A histological examination of lung specimens obtained by using a bronchoscope revealed a caseous granulomatous inflammation with an appearance of Langhans cells. The patient was treated using combined mycobacterium chemotherapy with an initial positive response for 6 months; however, the disease progressed later. We suggest that an awareness of lobar pneumonic consolidation as a rare radiological finding in pulmonary MAC infection is important. Abstract : An 83‐year‐old man with lobar caseous pneumonia by pulmonary Mycobacterium avium infection is described. The radiological findings were predominantly composed of dense lobar consolidation without fibrocavitary or nodular bronchiectatic pattern, mimicking tuberculous caseous pneumonia. This case emphasizes the importance of awareness of lobar pneumonic consolidation as a rare radiological finding in pulmonary MAC infection.